ACTIVATION OF SYNTHESIS OF ENDOGENOUS INTERFERON (REVIEW) - V. V. Poloskov; F. I. Ershov (Разработка и регистрация лекарственных средств)
The review is dedicated to the description of interferon inducers - new generation drugs created by Russian scientists as a result of the screening of thousands of high- and low-molecular synthetic and natural compounds. The drugs selected for clinical applications have a common ability to induce synthesis of endogenous interferons (IFN) after introduction into the organism. The main advantage of interferon inducers is a wide spectrum of antiviral activity, which is based on etiotropic and immunomodulatory effects of this group of drugs. Special attention is paid to the results of clinical application of interferon inducers.